Production of immunoreactive chorionic gonadotropin during mixed lymphocyte reactions: a possible selective mechanism for genetic diversity. - Harbour-McMenamin, D (1986)
Maternal immunologic recognition of the blastocyst as well as the hormone chorionic gonadotropin (CG) has been shown to be a requirement for successful implantation of the blastocyst and maintenance of the fetal graft. On the basis of these observations, we tested whether lymphocytes could produce chorionic gonadotropic-like hormones during a mixed lymphocyte reaction (MLR). Here we described the production of immunoreactive chorionic gonadotropin (ir-CG) as a result of an allogeneic stimulus but not other mitogenic stimuli. The kinetics of production, as monitored by immunofluorescence with antibody specific to the beta chain of the human CG (hCG) molecule, paralleled the blastogenic response. Gel filtration of the de novo-synthesized ir-CG showed the molecular weight of the intact molecule to be approximately 58,000. This molecule bound to a concanavalin A affinity column and also dissociated into two subunits of approximate molecular weights 32,000 and 18,000. These molecular weights are consistent with reported molecular weights for glycosylated intact hCG, as well as the beta and alpha chains of hCG, respectively. The material from the MLR but not the control cultures elicited significant testosterone production from Leydig cells, and this activity could be blocked by antiserum to hCG. The results described here, together with the fact that the blastocyst is implanted in a lymphocyte infiltrate, lend support to our postulate that lymphocyte-derived CG enhances successful implantation of the allogeneic fetus, thus providing a mechanism for selection of genetic diversity.